The Influence of Digital Marketing Strategies on MSME Consumer Purchasing Decisions in Ambon City: Multiple Regression Analysis Approach - Salhuteru, Andrie Christina; Hursepuny, Harold; Alvian Sapulette (Digital Innovation : International Journal of Management, 2026)
The rapid development of the digital ecosystem has encouraged Micro, Small, and Medium Enterprises (MSMEs) in Ambon City to adopt online platform-based marketing strategies in response to changing consumer behavior that is increasingly digitally connected. This research focuses on MSME consumers in Ambon City who actively interact with local business products through digital platforms. The main problems identified include low digital marketing adoption by local MSME actors, limited empirical studies on Eastern Indonesia context, and the absence of an integrative analytical model that simultaneously tests three dimensions of digital marketing. This research aims to analyze the influence of digital marketing strategies encompassing social media marketing, paid digital advertising, and content marketing on consumer purchasing decisions of MSMEs in Ambon City. This study employs a quantitative approach with a survey design involving 100 respondents selected through purposive sampling, and data were analyzed using multiple regression analysis after passing classical assumption tests covering normality, multicollinearity, and heteroscedasticity. Results show that social media marketing has a significant effect with a regression coefficient of 0.387, paid digital advertising with a coefficient of 0.312, and content marketing with a coefficient of 0.274, all significant at the 0.05 level. Simultaneously, the three variables explain 67.1% of variation in consumer purchasing decisions with an F-count of 65.847. Social media marketing is proven as the most dominant dimension shaping consumer purchasing decisions of MSMEs in Ambon City. This research concludes that an integrated and contextual digital marketing strategy is a crucial instrument in driving MSME growth in Eastern Indonesia and recommends strengthening digital capacity of local business actors as a priority policy for regional MSME empowerment.Keywords: digital marketing; purchasing decision; MSMEs; social media; Ambon City